2020
DOI: 10.1111/jdv.16801
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent chilblains and retinal vasculitis in a child with COVID‐19

Abstract: Dear Editor, Reports on COVID-19 in children are limited. Despite new data emerging, and understanding of the disease improves rapidly, there are as yet several features and complications related to the disease that remain unknown. Herein, we report the first case of a child with chilblains and retinal vasculitis related to COVID-19. An 11-year-old patient arrived at the Dermatology Emergency Department with a 2-week history of asymptomatic plaques on his toes. He did not complain of fever, respiratory symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 9 publications
1
37
0
6
Order By: Relevance
“…Nevertheless, some viruses such as Dengue and Chikungunya are known to cause retinal vasculitis, usually after acute infection, as shown in our patient (Lee et al 2017). Retinal vasculitis has also been reported in KD (12), but our patient didn´t develop any other manifestation of PIMS, as none of the patients with PIMS in our study had retinal vasculitis.…”
Section: ; Choi Et Al 2015; Fernandez-cooke Et Al 2019)supporting
confidence: 52%
See 1 more Smart Citation
“…Nevertheless, some viruses such as Dengue and Chikungunya are known to cause retinal vasculitis, usually after acute infection, as shown in our patient (Lee et al 2017). Retinal vasculitis has also been reported in KD (12), but our patient didn´t develop any other manifestation of PIMS, as none of the patients with PIMS in our study had retinal vasculitis.…”
Section: ; Choi Et Al 2015; Fernandez-cooke Et Al 2019)supporting
confidence: 52%
“…29% of patients presented red eye and they were diagnosed by slit lamp examination of: mild acute bilateral conjunctivitis (3 patients) and unilateral episcleritis (2 patients) ( Figure.1). Ocular fundus exam was normal in all patients, but in one of them, with unilateral retinal vasculitis, perivascular in ltrates and retinal exudates (Case 1) (12). OCT exam showed preserved macular and optic nerve head architecture in all patients, without any in ammatory signs.…”
Section: Resultsmentioning
confidence: 85%
“…Quintana-Castenedo et al [12] reported retinal vasculitis with perivascular infiltrate and retinal exudates in ocular fundus examination of a child with COVID-19, they did not describe vascular obstruction in the retinal vessels. Besides the clinical presentation in children is milder, we considered that sublingual evaluation provides a more 13 (100) Tidal volume (ml), mean ± sd 374 ± 66 PEEP (cm of water), mean ± sd 12 ± 3 Plateau pressure (cm of water), mean ± sd 24 ± 4 Static compliance (ml/cm of water), mean ± sd 33 ± 8 Respiratory rate (cycles/min), mean ± sd 24 ± 4 FiO2 (%), range (min-max) 0.55-1.00 Drugs Norepinephrine, n (%) 6 (46) Midazolam, n (%) 13 (100) Fentanyl, n (%) 13 (100) Neuromuscular blocking agent, n (%) 13 (100) Hydroxychloroquine, n (%) 3 (23) Macrolide antibiotic, n (%) 13 (100) Corticosteroids, n (%) 9 (69) Antiplatelet agents, n (%) 0 (00) Therapeutic LMWH, n (%) 6 (46) Prophylactic LMWH, n (%) 7 detailed assessment of microcirculation than funduscopic examination.…”
Section: Discussionmentioning
confidence: 95%
“…Quintana-Castenedo et al [ 12 ] reported retinal vasculitis with perivascular infiltrate and retinal exudates in ocular fundus examination of a child with COVID-19, they did not describe vascular obstruction in the retinal vessels. Besides the clinical presentation in children is milder, we considered that sublingual evaluation provides a more detailed assessment of microcirculation than funduscopic examination.…”
Section: Discussionmentioning
confidence: 99%
“…The highly sulfated state results in a negative density and binding capacity for a variety of positively charged ligands. A partial but representative summary of individual sites of vasculitis is provided (Table 1) [ [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69].…”
Section: Vasculitis In Covid-19mentioning
confidence: 99%